2020
DOI: 10.1101/2020.11.02.364273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

D614G substitution enhances the stability of trimeric SARS-CoV-2 spike protein

Abstract: SARS-CoV-2 spike protein with D614G substitution has become the dominant variant in the ongoing COVID-19 pandemic. Several studies to characterize the new virus expressing G614 variant show that it exhibits increased infectivity compared to the ancestral virus having D614 spike protein. Here, using in-silico mutagenesis and energy calculations, we analyzed inter-residue interaction energies and thermodynamic stability of the dominant (G614) and the ancestral (D614) variants of spike protein trimer in closed an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Coarse-grained normal mode analyses combined with Markov model and computation of transition probabilities characterized the dynamics of the S protein and mutational variants, predicting the increase in the open state occupancy for the more infectious D614G mutation due to the increased flexibility of the closed state and the enhanced rigidification of the open spike form (Teruel et al, 2020). Computer-based mutagenesis and energy analysis of the thermodynamic stability of the S-D614 and S-G614 proteins in the closed and partially open conformations showed that local interactions near D614 position are energetically frustrated and may create an unfavorable environment that is stabilized in the S-G614 mutant through strengthening of the inter-protomer association between S1 and S2 regions (Yazhini et al, 2020). Using time-independent component analysis (tICA) and protein graph connectivity network, another computational study identified the hotspot residues that may exhibit long-distance coupling with the RBD opening, showing that the D614G could exert allosteric effect on the flexibility of the RBD regions (Ray et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Coarse-grained normal mode analyses combined with Markov model and computation of transition probabilities characterized the dynamics of the S protein and mutational variants, predicting the increase in the open state occupancy for the more infectious D614G mutation due to the increased flexibility of the closed state and the enhanced rigidification of the open spike form (Teruel et al, 2020). Computer-based mutagenesis and energy analysis of the thermodynamic stability of the S-D614 and S-G614 proteins in the closed and partially open conformations showed that local interactions near D614 position are energetically frustrated and may create an unfavorable environment that is stabilized in the S-G614 mutant through strengthening of the inter-protomer association between S1 and S2 regions (Yazhini et al, 2020). Using time-independent component analysis (tICA) and protein graph connectivity network, another computational study identified the hotspot residues that may exhibit long-distance coupling with the RBD opening, showing that the D614G could exert allosteric effect on the flexibility of the RBD regions (Ray et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous mutagenesis analysis suggested that the D614G mutant may improve the stability of the S protein by strengthening the inter-protomer association between S1 and S2 regions. 53 We employed the equilibrium ensembles generated by MD simulations of the SARS-CoV-2 protein structures to perform deep mutational scanning of the spike protein residues and mutational sensitivity analysis of the D614 S trimer (Figure 4) and G614 S mutant proteins (Figure 5). Using energetic perturbation analysis, we test the shedding hypothesis suggesting that stabilization of the S-G614 protein may preclude a premature dissociation of the S1 subunit, leading to the increased number of functional spikes and stronger infectivity.…”
Section: Resultsmentioning
confidence: 99%
“…52 Computer-based mutagenesis and energy analysis of the thermodynamic stability of the S-D614 and S-G614 proteins in the closed and partially open conformations showed that local interactions near D614 position are energetically frustrated and may create an unfavorable environment that is stabilized in the S-G614 mutant through strengthening of the inter-protomer association between S1 and S2 regions. 53 Using time-independent component analysis (tICA) and protein graph connectivity network, another computational study identified the hotspot residues that may exhibit long-distance coupling with the RBD opening, showing that the D614G could exert allosteric effect on the flexibility of the RBD regions. 54 Structure-based physical model showed that the D614G mutation may induce a packing defect in S1 that promotes closer association and stronger interactions with S2 subunit, thereby supporting the reduced shedding hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous mutagenesis analysis suggested that the D614G mutant may improve the stability of the S protein by strengthening the inter-protomer association between S1 and S2 regions. 53 We employed the equilibrium ensembles generated by CABS-CG simulations of the SARS-CoVstructures to perform alanine scanning of the protein residues and mutational sensitivity analysis of the S-D614 and S-G614 proteins at the mutational site ( Figure 5). The primary objective of this energetic analysis was to further test the shedding hypothesis suggesting that D614G may lead to stabilization of the S protein and block a premature dissociation of the S1 subunit, leading to the increased number of functional spikes and stronger infectivity.…”
Section: Differential Stabilization Of the Closed And Open Statesmentioning
confidence: 99%
“…50 By applying a differential contact analysis, this study argue that contacts in CTD1-CTD2 (528-685) and FP-FPPR strengthening of the inter-protomer association between S1 and S2 regions. 53 Using timeindependent component analysis (tICA) and protein graph connectivity network, another computational study identified the hotspot residues that may exhibit long-distance coupling with the RBD opening, showing that the D614G could exert allosteric effect on the flexibility of the RBD regions. 54 Structure-based physical model showed that the D614G mutation may induce a packing defect in S1 that promotes closer association and stronger interactions with S2 subunit, thereby supporting the reduced shedding hypothesis.…”
mentioning
confidence: 99%